Presence of Serum Antinuclear Antibodies Does Not Impact Outcomes in HBV-Related Acute-on-Chronic Liver Failure - Lin Lin; Bin Lin; Qing Lan; Longgen Liu; Jianchun Lu; Xiujun Zhang; Shuqin Zheng; Yuan Xue (Canadian Journal of Gastroenterology and Hepatology)
Background. The aim of this study was to provide new insights into the prevalence of positive antinuclear antibody (ANA) in patients with HBV-related acute-on-chronic liver failure (ACLF) and its impact on clinical outcomes. Methods. A total of 116 patients with HBV-related ACLF treated at three clinical centers were retrospectively recruited. Serum concentrations of ANA were detected using the enzyme-linked immunosorbent assay kit. Multiple nuclear dots, rim-like, and centromere patterns of ANA were detected using indirect immunofluorescence assay on HEp-2 cells. Results. Among the 116 patients with HBV-related ACLF, 17 (14.66%) were ANA positive. Most patients in both ANA positive and negative groups were males (88.2% and 83.8%). Patients with negative ANA had a higher international normalized ratio, model for end-stage liver disease (MELD), and MELD-sodium scores than those with positive ANA (all P<0.05). Multiple nuclear dot pattern was detected in half of the patients (8/17, 47.06%), rim-like/membranous pattern was found in six patients, and centromere pattern was detected in the last three patients. For patients with ANA (+), IgM was lower, and it was positively correlated with IgG. For patients with ANA (-), C3 was positively correlated with C4, and both C3 and C4 were negatively correlated with INR and MELD (all P<0.05). In addition, TBIL, INR, WBC, and PLT, but not ANA, resulted as independent risk factors associated with 90-day mortality. Conclusion. Positive ANA is frequent in HBV-related ACLF, and it does not seem to be associated with poor outcomes, but the pathogenesis of ACLF may be different between ANA (+) and ANA (−) groups.